Values, bioactive compound, antioxidant activities of brown rice and germinated brown rice, and the pellet products - Preecharram, Sutthidech; Posoongnoen, Saijai; Thummavongsa, Theera; Pasom, Witchuda; Panyakom, Sirin; Sripakdee, Thitiya; Jandaruang, Jinda (Creative Science, 2024)
This study aimed to explore the dietary components, phenolic compounds, GABA content, and antioxidant capacity of brown rice and germinated brown rice from two rice varieties: the glutinous rice variety Kor Khor 6 (RD6) and the paddy rice type Hom Mali 105 rice. The study findings indicated that protein composition varied between 6.76 – 7.91%, fat content ranged from 2.49 – 2.85%, and carbohydrate content varied from 73.65 – 79.83%. The average energy value is 362 kcal 100 g –1. Germinated brown rice of Hom Mali 105 has the highest GABA levels with 4.70 mg 100 g–1 dry weight. The Hom Mali 105 exhibited the highest levels of phenolic compounds, registering at 0.5 mg 100 g–1 dry weight. Germinated brown rice of Hom Mali 105 has the highest capacity to bind to DPPH free radicals and Fe2+, which IC50 values of 7.12 and 82.00 mg mL–1, respectively. Following the research on rice pelleting, the result of pellets was discovered to be completely round and undamaged. This study shows that brown rice and germinated brown rice are good sources of nutrients and energy. They also possess potent antioxidant qualities. Preliminary rice powder pellets were produced from germinated brown rice of Hom Mali 105. These rice pellets can be molded into uniquely shaped products. The solid density, water absorption, and hardness of the rice pellets were measured at 1.12 ± 0.05 g cm-³, 3.83 ± 1.02 %, and 57.86 ± 5.88 N, respectively. These pellets are easy to consume and offer a complete range of nutrients. GRAPHICAL ABSTRACT HIGHLIGHTS Brown rice and germinated brown rice has high proximate composition, phenolic compounds, antioxidant activity and gamma aminobutyric acid. Rice powder pellets can be shaped into products with unique shapes. This dish is simple to eat and provides complete nutrients.